Clinical profile of patients with acute coronary syndrome with special reference to diabetes mellitus - Chahare, Vinod Wasudeo; Ray, Tapas; Bhattacharya, Chandramouli; Wankar, Abhinav Dileep (International Journal of Research in Medical Sciences, 2017)
Background: Ischemic heart disease is defined as inadequate blood flow resulting in decreased oxygenation to the myocardium due to severe narrowing and/or complete blockage of coronary arteries. Although a number of risk factors have been identified over the past several decades, the precise aetiology and mechanisms leading to the development of CAD are not fully understood. These includes abnormal levels of circulating cholesterols with elevated level of LDL-cholesterol and reduced level of HDL-cholesterol, hypertension, cigarette smoking, diabetes mellitus, male gender, post-menopausal state, advanced age, sedentary life style, obesity and a positive family history of premature cardiovascular disease female population. Methods: Our study was aimed to interrogate and to assess the patients presenting with acute coronary syndrome, for the presence of conventional risk factors with special eye on diabetes and to stratify patients with acute coronary syndrome according to their diabetic status (Diabetic vs. non diabetic) and also to study pattern of involvement of coronary arteries in diabetic and non-diabetic patients and to stratify patient according to treatment they received PTCA vs. CABG. Results: It was observed that out of 100 patients with diabetes mellitus, 71% patients were having diabetes mellitus. Among the diabetics in this study, STEMI (73.13%) was the commonest presentation of ACS. On the other hand amongst diabetics, 58.33% had STEMI. Conclusion: Patients with diabetes mellitus had more dyslipidemia, hypertension and smokers. This group of patients required maximum intervention in the form PTCA and CABG.